2021
DOI: 10.3389/fsoil.2021.692583
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Approach to Isolate Slow and Fast Cycling Organic Carbon Fractions in Central European Soils—Importance of Dispersion Method

Abstract: Numerous approaches have been developed to isolate fast and slow cycling soil organic carbon (SOC) pools using physical and chemical fractionation. Most of these methods are complex, expensive, and time consuming and unsuited for high-throughput application, such as for regional scale assessments. For simpler and faster fractionation via particle size the key issue is the dispersion of soil. It is unclear how the initial dispersion of soil affects the turnover rates of isolated fractions. We investigated five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…This fraction was chosen with the aim of keeping the soil organic matter model simple (two pools), considering it as functionally representing the fast cycling/labile organic C pool (53)(54)(55). Although mechanical dispersion methods such as shaking with glass beads have been reported to be more adequate for the isolation of this fraction, they seem not to be adequate in clay and carbonate-rich soils (56). The use of a (NaPO 3 ) 6 solution of pH 6.13 was therefore preferred, and the risk of organic C loss from this fraction by dissolution was minimized by reducing rinsing as much as possible.…”
Section: Analytical Methods and Soc Storage Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…This fraction was chosen with the aim of keeping the soil organic matter model simple (two pools), considering it as functionally representing the fast cycling/labile organic C pool (53)(54)(55). Although mechanical dispersion methods such as shaking with glass beads have been reported to be more adequate for the isolation of this fraction, they seem not to be adequate in clay and carbonate-rich soils (56). The use of a (NaPO 3 ) 6 solution of pH 6.13 was therefore preferred, and the risk of organic C loss from this fraction by dissolution was minimized by reducing rinsing as much as possible.…”
Section: Analytical Methods and Soc Storage Determinationmentioning
confidence: 99%
“…The fact that the parallel model (Figure 7) was a closer approximation to actual SOC dynamics in the studied soil than the sequential model option (Figure 6) suggested that, in the soil and cropping conditions of this experiment, the protection of organic C from crop residues can be direct, once they are incorporated into the soil. This can however also been partially explained if a small fraction of the labile fraction POC 50−2,000 was transferred to the non-labile fraction in the fractionation process, as suggested by one recent re-assessment of different methodologies to isolate slow and fast cycling SOC fractions (56) We reduced rinsing, and used a non-alkaline solution, to minimize this aspect, but it is still possible that part of the most labile fraction was indeed accounted for in the non-labile fraction in our case.…”
Section: Modeling Soc Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…and tested for routine analysis of large sample sets to obtain indicators for soil management and OC input strategies (Just et al, 2021;.…”
Section: Isolation Of Particulate Organic Matter and Organomineral As...mentioning
confidence: 99%
“…Different extractants have been found to systematically bias soil protein extraction (Bastida et al, 2018;Greenfield et al, 2018;Masciandaro et al, 2008). Particulate organic matter (POM) and mineral-associated organic matter (MAOM) fractions have been related to turnover times of conceptual soil organic C pools (Just et al, 2021;Peralta et al, 2022;Zimmermann et al, 2007). To date, knowledge gaps exist with regard to the relative importance of protein functions and taxonomy pertaining to the nature of extracted SOM fractions.…”
Section: Introductionmentioning
confidence: 99%